USP12 downregulation orchestrates a protumourigenic microenvironment and enhances lung tumour resistance to PD-1 blockade - Zhaojuan Yang (Nature Portfolio, 2021)
The cancer cell-extrinsic roles of deubiquitinases are unclear. Here the authors show that deubiquitinase USP12 downregulation contributes to development of an immune-suppressive tumour microenvironment in KRAS-driven lung cancers and mechanistically this is through the insufficient deubiquitination of the NF-κB inhibitor, PPM1B.